MAKE SERVICE CATALOGUE MANAGEMENT USING ITIL IN PPTI INSTITUT BISNIS DAN INFORMATIKA STIKOM SURABAYA - Feriyan, Feriyan; Sutomo, Erwin; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Development and Application of Information Technology (PPTI) is one part in the Institute of Business and Informatics Stikom Surabaya (Stikom). PPTI has the responsibility to develop and implement Information and Communication Technology (ICT) in Stikom Surabaya. PPTI has a wide range of services provided to users. However, PPTI still have not had a service catalogue. Service catalogue is needed to control and evaluate the services provided to users. Based on these problems, it is necessary to make a service design draft to meet the needs of the service catalogue. The service design is based on Service Design standard in the framework of the Information Technology Infrastructure Library (ITIL v3). This research resulted in the business impact analysis document, service policy, the service description and service catalogue. The resulting document will be useful as a reference to control and evaluate the services provided to users.